The evolution of research on academic procrastination during Covid-19: A visual analysis using VOSviewer and Biblioshiny - Fitriani, Wahidah; Putri, Rahayu Eka; Kamarudin, Diyana; Mudinillah, Adam (Universitas Mercu Buana Yogyakarta, 2023)
Several students have experienced academic procrastination, particularly in the context of the Covid-19 pandemic. Previous research has been conducted to understand the relationship between academic procrastination and a range of variables, including self-regulated learning, academic stress, and achievement. However, a significant gap exists in terms of analyzing the broader patterns and trends in this field through bibliometric analysis. Therefore, this study aimed to provide a complete picture of academic procrastination and explore hot spots and research trends during Covid-19. The bibliometric VOSviewer and Biblioshiny methods were used to analyze academic procrastination literatures in the Scopus core collection database. The overall characteristics of academic procrastination during this period were summarized by analyzing numbers, published research, countries, institutions, and keywords. A total of 141 articles published in the Scopus database from 2020 to 2022 were analyzed. The result showed the most influential countries were China, Turkey, as well as Indonesia and the United States, which took a prominent lead with 29, 16, and 13 articles published, respectively. UniversitÃ¤t Paderborn emerged as the most productive institution, having published 5 articles during covid-19. With the aid of VOSviewer and Biblioshiny tools, this research identified the hotpots of academic procrastination, which were mainly associated with the title analysis, namely self-efficacy, academic motivation, academic achievement, life satisfaction, university students, academic hardiness, psychological wellbeing, followed by self-regulation, anxiety, and internet addiction. Therefore, this research was very useful for scholars and practitioners to comprehensively understand the trend of research on academic procrastination during Covid-19.